2008
DOI: 10.2147/ijn.s2322
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nano MgO and BaSO4 particle size additives on properties of PMMA bone cement

Abstract: Abstract:A common technique to aid in implant fi xation into surrounding bone is to inject bone cement into the space between the implant and surrounding bone. The most common bone cement material used clinically today is poly(methyl methacrylate), or PMMA. Although promising, there are numerous disadvantages of using PMMA in bone fi xation applications which has limited its wide spread use. Specifi cally, the PMMA polymerization reaction is highly exothermic in situ, thus, damaging surrounding bone tissue whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Different percentages of BSGs were added to PMMA to understand the effect of BSGs on the polymerization of PMMA, where the BSGs could potentially inhibit the polymerization, weakening its strength. 51 This study found that the addition of 10% of BSGs was the most optimal. At this concentration, the BSGs released optimal concentrations of ions of boron or strontium and provided an alkaline pH microenvironment of about 8, inhibiting osteoclast activity and enhancing osteoblast activity.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Different percentages of BSGs were added to PMMA to understand the effect of BSGs on the polymerization of PMMA, where the BSGs could potentially inhibit the polymerization, weakening its strength. 51 This study found that the addition of 10% of BSGs was the most optimal. At this concentration, the BSGs released optimal concentrations of ions of boron or strontium and provided an alkaline pH microenvironment of about 8, inhibiting osteoclast activity and enhancing osteoblast activity.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, this study synthesized a composite, 10-BSG/PMMA, to improve the bioactivity of PMMA without adversely affecting its mechanical properties. Different percentages of BSGs were added to PMMA to understand the effect of BSGs on the polymerization of PMMA, where the BSGs could potentially inhibit the polymerization, weakening its strength . This study found that the addition of 10% of BSGs was the most optimal.…”
Section: Discussionmentioning
confidence: 90%
“…The hydrolysis-resistant titanium–bone cement interface, has been, furthermore, proven to counteract aseptic loosening by modifying the cement substrate with methacryloxypropyl-trimethoxysilane [48]. Other bone cement additives that have been put to test are microhydroxyapatite, -magnesium oxide, -barium sulphate and -silica particles [15,36,37], as well as methacrylate crosslinkers ethylene glycol-dimethacrylate (EG-DMA) [15,57,58] or hydroxyethyl methacrylate (HEMA) [15,59], and finally, triethylene glycol-dimethacrylate (TEG-DMA) [15,60,61]. PMMA cement supplementation with vancomycin was assessed in the study by Ajit Singh et al [30], who concluded that even a 2 g addition of the drug per a 40 g container of cement (5% by weight) significantly affects the degradation of the three-point bending flexural strength.…”
Section: Discussionmentioning
confidence: 99%
“…Far too little attention has been paid to the effect of contamination on the cement strength properties, in particular in the presence of human blood [34]. The focus of bone-cement studies is on admixtures of auxiliary agents, supplied to improve the material’s properties, including strength [22,26,33,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The polymethyl methacrylate (PMMA) bone cement 5–7 and calcium phosphate cement (CPC) have been used clinically as bone repair materials 8–12 . Although PMMA bone cements are used in most clinical treatments for orthopedic implants due to their high strength and good plasticity, PMMA bone cements still suffer from the potential risk of massive exothermic reaction in curing process and monomeric cytotoxicity 13,14 . In addition, comparing to hydroxyapatite (HA) or CPC, the biocompatibility and biomineralization properties of PMMA need to be further improved.…”
Section: Introductionmentioning
confidence: 99%